Analysis of the relationship between inundation frequency and wetland vegetation in Dongting Lake using remote sensing data. Issue 2 (15th May 2013) - Deng, Fan; Wang, Xuelei; Cai, Xiaobin; Li, Enhua; Jiang, Liuzhi; Li, Hui; Yan, Ranran
ABSTRACT Hydrological characteristics significantly drive the formation of and variations in wetland vegetation. Given increasing impact from human activities and climate change, the hydrological regime has become exceedingly unstable, thereby heavily affecting the distribution and dynamics of wetland vegetation. The relationship between inundation frequency – an important hydrological factor – and vegetation community distribution in Dongting Lake was analysed to depict how the hydrological regime determines the distribution of wetland vegetation cover. Wide tempo‐spatial scales were used to calculate the inundation frequency in the lake and to compare the distribution patterns of the communities. For the implementation of the aforementioned tasks, this study provides remote sensing‐ and geographical information system‐based methods. The responses of individual vegetation communities to inundation frequency differ depending on their specific physiological characteristics. Wood and reed communities are more suitable for regions with low inundation frequency, whereas grass and lake‐grass communities are more adaptable to areas of high inundation frequency. The variations in inundation frequency may explain the succession of vegetation communities, which occurs when inundation frequency decreases with increasing wood and reed communities. These results can serve as support for evaluating the impact of hydrological changes on the community structures and distributions of wetland vegetation. Copyright © 2013 John Wiley & Sons, Ltd.